GNA14 may be a potential prognostic biomarker in nasopharyngeal carcinoma - Hao, Jinrong; Yu, Xia; Xiong, Lei; Deng, Li; Lian, Shifeng; Sun, Shijun; Li, Xiaoling; Du, Yun; Ji, Mingfang (Frontiers in Oncology, 2024)
BackgroundNasopharyngeal carcinoma (NPC) is a highly invasive malignant tumor. Recurrence and distant metastasis represent the primary causes of treatment failure. This study aimed to identify biomarkers highly associated with NPC and investigate its roles in tumor progression.MethodsTranscriptome sequencing (RNA-seq) data of NPC and normal tissues were downloaded from the Gene Expression Omnibus (GEO) database. By analyzing the RNA-seq data, we found that G Protein Subunit Alpha 14 (GNA14) is closely associated with the diagnosis and prognosis of NPC. Immunohistochemistry (IHC) was used to detect the expression of GNA14 in tumor tissues of 165 NPC patients, and we analyzed the relationship between GNA14 expression and patient prognosis. The potential mechanisms by which GNA14 affects tumor prognosis were preliminarily analyzed using bioinformatics analysis.ResultsAnalysis of RNA-seq data and IHC showed that GNA14 expression was downregulated in NPC (p < 0.001, p < 0.01, respectively), and low expression of GNA14 was closely associated with poor prognosis. IHC analysis showed that patients with low GNA14 expression had significantly shorter progression-free survival (PFS) and distant metastasis-free survival (DMFS) than those with high GNA14 expression (p = 0.023, p = 0.008, respectively). Multivariate analysis indicated that the GNA14 expression was an independent risk factor for DMFS (p = 0.030). The DMFS nomogram included GNA14 expression, EBV DNA, and N stage as prognostic factors and the concordance index (C-index) of the nomogram was 0.73. Bioinformatics analysis indicated that NPC patients with low GNA14 expression might represent lower levels of immune cell infiltration and poorer drug sensitivity.ConclusionLow GNA14 expression may be a risk factor for poor prognosis in NPC.